2015
DOI: 10.1039/c5em00212e
|View full text |Cite
|
Sign up to set email alerts
|

Propane biostimulation in biologically activated carbon (BAC) selects for bacterial clades adept at degrading persistent water pollutants

Abstract: Biologically activated carbon (BAC) can be used in both municipal water and hazardous waste remediation applications to enhance contaminant attenuation in water; however, questions remain about how selective pressures can be applied to increase the capabilities of microbial communities to attenuate recalcitrant contaminants. Here we utilized flow-through laboratory columns seeded with municipally derived BAC and exposed to water from a local drinking water facility to query how propane biostimulation impacts r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Interestingly, the highest population diversities were in the top samples ( Fig S2) where a significant decrease with depth was found in both columns (Kruskal-Wallis H Test, both P< 0.001). Similar phenomena were observed in a previous pilot-scale up-flow BAC filtration system treating lake water with pre-ozonation, in which a marked decrease of microbial diversity in the BAC filtration system was observed along the flow path (Liao et al, 2012) and a lab scale BAC filtration system (Mikkelson et al, 2015). In contrast, a converse trend with increasing diversity during biofiltration transit has been observed in sand sediment columns exposed to surface and wastewaters (Li et al, 2012 and.…”
Section: Microbial Community Profile and Spatial Trendssupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, the highest population diversities were in the top samples ( Fig S2) where a significant decrease with depth was found in both columns (Kruskal-Wallis H Test, both P< 0.001). Similar phenomena were observed in a previous pilot-scale up-flow BAC filtration system treating lake water with pre-ozonation, in which a marked decrease of microbial diversity in the BAC filtration system was observed along the flow path (Liao et al, 2012) and a lab scale BAC filtration system (Mikkelson et al, 2015). In contrast, a converse trend with increasing diversity during biofiltration transit has been observed in sand sediment columns exposed to surface and wastewaters (Li et al, 2012 and.…”
Section: Microbial Community Profile and Spatial Trendssupporting
confidence: 85%
“…This phylogenic profile is consistent with nitrate formation during BAC transit as described in the prior section. Analogously, Nitrospira were found in the top layers (0.3 m below the surface) of two BAC columns that received ozone treated water (accounting for 3.4% and 5.3% of total microbial population) in a previous study (Liao et al, 2013b) and were dominant (5.1% of total microbial population) in the top layer of a BAC column receiving tap water (Mikkelson et al, 2015). Planctomyces species belong to the phylum Planctomycetes, which hosts guilds capable of anammox metabolism (Kartal et al, 2013), were abundant in the top samples of both columns (3.4% and 1.0%, respectively), suggesting a potential interplay with Nitrospira.…”
Section: Microbial Community Profile and Spatial Trendsmentioning
confidence: 54%
See 1 more Smart Citation
“…Lastly, our community analysis results clearly demonstrated that AOM and MC-LR could impact the community structure of biofilm, increasing the relative abundance of bacteria that potentially utilize AOM components and MC-LR. Our finding displays the future potential to harness biofilm activity and functions in BAF for enhanced removal of cyanobacteriaderived contaminants using feasible strategies such as biostimulation and/or bioaugmentation (Horemans et al, 2017;Mikkelson et al, 2015).…”
Section: Engineering Implicationsmentioning
confidence: 91%